A Brief History of Cannabis and the Drug Conventions - John Collins (AJIL Unbound, 2020)
“Drugs” have been regulated at the international level since 1912, while cannabis has been specifically regulated since 1925. Contemporary local, national, and international cannabis regulations are now diverging, with some jurisdictions legalising its recreational production, sale and consumption. This essay explores the legal and historical complexity and contingencies around the development of international cannabis regulations and prohibitions. It highlights that the global drug control system was not solely focused on prohibition and instead was a complex mix of regulations underpinned by frequently ill-defined and unclear prohibitions. It argues that the international drug control system should not serve as a bar to national-level reforms and that the two can continue to coexist. The essay favors a flexible, functional and pragmatic interpretation and implementation of the system as the most likely and indeed preferred outcome of international cannabis policy reforms.